2016
DOI: 10.1007/978-3-319-31165-4_2
|View full text |Cite
|
Sign up to set email alerts
|

XaaS Multi-Cloud Marketplace Architecture Enacting the Industry 4.0 Concepts

Abstract: Cloud computing in conjunction with recent advances in Cyber-Physical Systems (CPSs) unravels new opportunities for the European manufacturing industry for high value-added products that can quickly reach the market for sale. The Internet of Things joins the Internet of Services to enact the fourth industrial revolution that digitalises the manufacturing techniques and logistics while pushing forward the development of improved factories with machine-to-machine communication delivering massively customised pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It makes manufacturing more agile through servitization by integrating resources and capability, such as technology, thus making the technology of the company agile as well. Therefore, it is concluded that more and more companies adopt cloud computing technologies to increase agility within organizations [99], as the literature clearly supports the evidence of cloud computing and agility [100].…”
Section: Cloud Computingmentioning
confidence: 99%
See 1 more Smart Citation
“…It makes manufacturing more agile through servitization by integrating resources and capability, such as technology, thus making the technology of the company agile as well. Therefore, it is concluded that more and more companies adopt cloud computing technologies to increase agility within organizations [99], as the literature clearly supports the evidence of cloud computing and agility [100].…”
Section: Cloud Computingmentioning
confidence: 99%
“…The IoT is one of the most important parts of Industry 4.0 ecosystem [121], and transitioning from traditional to Industry 4.0 environment requires the implementation of IoT and platforms [122]. Moreover, IoT platforms are also instruments used in enhancing the organizational agility [100] as they increase the agility of organizations with respect to the process [60], information system [91], facility [89], flexibility [71], management [117], manufacturing [61] and technology [79]. The embedding of (organizational) objects with the internet creates communication between them, and these objects start to exchange data among themselves [69], which results in the effective automation in the organization.…”
Section: Internet Of Things Platformsmentioning
confidence: 99%
“…The proposed work differs from others by implementing the architecture and addressing various aspects, including scalability and compatibility. A generic Cloud-based marketplace architecture is proposed in [8] to enable trading of IoT deployments. The architecture addresses the Cloud-IoT integration and vendor lock-in issues.…”
Section: A Iot Marketplace Architecturesmentioning
confidence: 99%
“…It is a mechanism for sharing information with collaborators. The cloud is characterized by its speed, which allows administrators to store data in the cloud and implement new systems to monitor and control processes through digital platforms [33].…”
Section: Technologies Of Industry 40mentioning
confidence: 99%